Fermentation and Functional Properties of Plant-Derived Limosilactobacillus fermentum for Dairy Applications - Batchimeg Namshir; Gil-Ha Kim; Natsag Lkhagvasuren; Seon-A Jeong; Narangerel Mijid; Woan-Sub Kim (Fermentation)
Lactic acid bacteria (LAB) isolated from plant sources are gaining increasing attention due to their potential probiotic and postbiotic functionalities. In the present study, Limosilactobacillus fermentum isolated from Prunus padus (bird cherry) was evaluated for its physiological, functional, and technological attributes for application in fermented dairy products. The strain was isolated through anaerobic fermentation and identified using API 50 CHL and 16S rRNA sequencing. Its acid tolerance, antioxidant capacity, antibacterial effects, and hemolytic activity were assessed. The cell-free supernatant (CFS) was evaluated for thermal and pH stability. Fermentation trials were conducted using both mono- and co-culture combinations with the commercial yogurt starter strain YC-380. Physicochemical properties, viable cell counts, and viscosity were monitored throughout fermentation and refrigerated storage. The L. fermentum isolate exhibited strong acid resistance (48.28% viability at pH 2.0), non-hemolytic safety, and notable DPPH radical scavenging activity. Its CFS showed significant antibacterial activity against five Escherichia coli strains, which remained stable after heat treatment. Co-cultivation with YC-380 enhanced fermentation efficiency and improved yogurt viscosity (from 800 to 1200 CP) compared to YC-380 alone. During 24 days of cold storage, co-cultured samples maintained superior pH and microbial stability. Additionally, the moderate acidification profile and near-neutral pH of L. fermentum created favorable conditions for postbiotic compound production. These results indicate that L. fermentum derived from P. padus holds considerable promise as a functional adjunct culture in yogurt production. Its postbiotic potential, technological compatibility, and heat-stable bioactivity suggest valuable applications in the development of safe, stable, and health-promoting fermented dairy products.